Ultrahigh conductivity in Weyl semimetal NbAs nanobelts - Zhang, Cheng; Ni, Zhuoliang; Zhang, Jinglei; Yuan, Xiang; Liu, Yanwen; Zou, Yichao; Liao, Zhiming; Du, Yongping; Narayan, Awadhesh; Zhang, Hongming; Gu, Tiancheng; Zhu, Xuesong; et al. (Nature materials, 2019)
In two-dimensional (2D) systems, high mobility is typically achieved in low-carrier-density semiconductors and semimetals. Here, we discover that the nanobelts of Weyl semimetal NbAs maintain a high mobility even in the presence of a high sheet carrier density. We develop a growth scheme to synthesize single crystalline NbAs nanobelts with tunable Fermi levels. Owing to a large surface-to-bulk ratio, we argue that a 2D surface state gives rise to the high sheet carrier density, even though the bulk Fermi level is located near the Weyl nodes. A surface sheet conductance up to 5–100 S per □ is realized, exceeding that of conventional 2D electron gases, quasi-2D metal films, and topological insulator surface states. Corroborated by theory, we attribute the origin of the ultrahigh conductance to the disorder-tolerant Fermi arcs. The evidenced low-dissipation property of Fermi arcs has implications for both fundamental study and potential electronic applications. High mobility and high carrier density are found in the Weyl semimetal NbAs. This is attributed to the low dissipation of disorder-tolerant Fermi arcs.